2012
DOI: 10.1021/ie301520v
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Gastropod Shell Derived Calcium Oxide in Clay and Application in Phosphate Removal from Aqua Medium

Abstract: The phosphate sorption potential of the layered framework of naturally occurring clay, which acts as a host in the sorption process, was boosted via intercalation of CaO derived from a Gastropod shell (GS). GS was used as precursor for the synthesis of the CaO in the perspective of waste recycling and cost minimization in environmental remediation. The phosphate sorption potential, PZC, and the surface area of raw clay sample were substantially enhanced by the intercalation process. The value of the Langmuir m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…By the intercalation of CaO into gastropod shell clays, high phosphate adsorption capacity of modied gastropod shell clay could be achieved. 12 Similarly, through the slow pyrolysis of Mg-enriched tomato tissues in an oxygen-decient environment, engineered biochar embedded with nanoscale Mg(OH) 2 and MgO is found to have a high phosphate adsorption capacity because these nanoparticles serve as the main adsorption sites for phosphate accommodation. 13 These interesting results clearly indicate that the appropriate acquisition of naturally abundant alkaline earth elements would be an environmentally friendly route to prepare high-performance adsorbents for the removal of phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…By the intercalation of CaO into gastropod shell clays, high phosphate adsorption capacity of modied gastropod shell clay could be achieved. 12 Similarly, through the slow pyrolysis of Mg-enriched tomato tissues in an oxygen-decient environment, engineered biochar embedded with nanoscale Mg(OH) 2 and MgO is found to have a high phosphate adsorption capacity because these nanoparticles serve as the main adsorption sites for phosphate accommodation. 13 These interesting results clearly indicate that the appropriate acquisition of naturally abundant alkaline earth elements would be an environmentally friendly route to prepare high-performance adsorbents for the removal of phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…This result was also found for the adsorption of phosphate by BS600, Ca-Mg-loaded biochar, and CaO-modified clay, respectively. [10,18,26] Consequently, the strong interaction between phosphate and CaO/MgO played a key role in the enhancement of phosphate adsorption.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…Bentonite modified with Mg(OH) 2 has a significant effect on the removal efficiency of phosphate, resulting in a maximum adsorption density of 14.33 mg m −2 . Similarly, the intercalation of CaO in a gastropod shell clay framework can enhance the phosphate adsorption capacity from the perspective of low cost and waste recycling . Previous study has also shown that the negatively charged bentonite (Na‐type MX‐80) surface can be well modified by the incorporation of seawater Ca/Mg via ion exchange, resulting in effective removal of phosphate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a pointer to the fact that the sorption of the CU(II) ions moieties on MMOL occurred via chemisorptions. If the sorbate uptake is chemically rate controlled, then the pseudo second order constants will be independent of particle diameter and flow rate will depend on concentration of the ions in solution [20]. A review of the results, presented in Tables 3, showed that the pseudo second order parameters obtained from the uptake of CU(II) ions onto MMOL (qe and k 2 values) varied with the initial CU (II) concentration.…”
Section: Sorption Kinetics Studiesmentioning
confidence: 99%